Research of the Sensitivity of the Quantized Coefficients of a Digital Bandpass Filters with Frequency Sampling - Rybka Serhii Volodуmуrovуch; Korolov Andrii Pavlovуch; Varava Ivan Andriiovуch (IAES Indonesian Section, 2020)
The article is devoted to the applied research of the dependence of the influence of the transfer function quantized coefficients of digital bandpass filters with frequency sampling on its attenuation characteristic. It is shown that only the coefficients, which depend on the frequency, when quantized, significantly distort the shape of the attenuation characteristic. Such coefficients in the article are called frequency coefficients. The magnitudes of the deviations of the quantized frequency coefficients from the calculated values at different values of the bit depth are analyzed. The attenuation characteristics of the digital comb of bandpass filters based on frequency sampling with calculated and quantized coefficients are analyzed. Practical recommendations are offered to minimize the influence of frequency coefficients quantization errors at the stage of solving the task of approximation of digital bandpass filters with frequency sampling. The result will be an optimal choice of the minimum number bit of the processors or programmable logic integrated circuits (FPGA), to be used for the implementation of digital bandpass filters with frequency sampling.